Secure Wireless Communications Based On Antenna Array Elements (International Journal of Technology and Management Research, 2020)
Configuration of antenna array system to offer directional dependent modulation has the capability of enhancing the security level of data transmission against eavesdroppers’ attacks. In this paper, Frequency diverse array (FDA) antenna for physical–layer security in wireless communications has been proposed. The proposed method provide a range and angle dependent directional modulation scheme using FDA with frequency increments to improve physical-layer security point-to-point communications. It maintains the objective of changing the progressive phase shifts at each symbol transmission. Thus the emitted pattern at each symbol transmission period will be range and angle dependent. Consequently, the proposed method offers a robust physical-layer security for wireless transmission, as the transmitted signal will be deliberately distorted along the undesired positions, but can be successfully decoded by the intended receiver position. Numerical results are presented to validate the effectiveness of the proposed method.Keywords: Frequency diverse array; Physical-layer security; Directional antenna modulation; Wireless communication; Range and angle dependent.